2018
DOI: 10.2967/jnumed.118.209387
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impact of 68Ga-PSMA-11 PET/CT on the Planning of Definitive Radiation Therapy for Prostate Cancer

Abstract: Standard-of-care imaging for initial staging of prostate cancer (PCa) underestimates disease burden. Prostate-specific membrane antigen (PSMA) PET/CT detects PCa metastasis with superior accuracy, having a potential impact on the planning of definitive radiation therapy (RT) for nonmetastatic PCa. Our objectives were to determine how often definitive RT planning based on standard target volumes covers Ga-PSMA-11 PET/CT-defined disease and to assess the potential impact ofGa-PSMA-11 PET/CT on definitive RT plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 35 publications
5
56
0
Order By: Relevance
“…With the exception of the recent Australian guidelines (8), most currently published guidelines do not recommend imaging for BCR at PSA levels of less than 1.0 ng/mL (7). This stance has been challenged recently, with several studies reporting high detection rates for recurrent disease in men with BCR at low PSA levels using PSMA PET (9)(10)(11)(12)(13)(14).The present study confirmed the high detection rates for disease recurrence using PSMA both in the PF and distantly. Consistent with the previous comparisons of 18 F-FCH and PSMA PET, the number of extra fossa lesions visualized on PSMA was higher than that visualized on 18 F-FCH in men who underwent imaging with both modalities (15,16).…”
Section: Discussionsupporting
confidence: 69%
“…With the exception of the recent Australian guidelines (8), most currently published guidelines do not recommend imaging for BCR at PSA levels of less than 1.0 ng/mL (7). This stance has been challenged recently, with several studies reporting high detection rates for recurrent disease in men with BCR at low PSA levels using PSMA PET (9)(10)(11)(12)(13)(14).The present study confirmed the high detection rates for disease recurrence using PSMA both in the PF and distantly. Consistent with the previous comparisons of 18 F-FCH and PSMA PET, the number of extra fossa lesions visualized on PSMA was higher than that visualized on 18 F-FCH in men who underwent imaging with both modalities (15,16).…”
Section: Discussionsupporting
confidence: 69%
“…Although patients before definitive radiotherapy constituted the smallest subgroup of the present cohort, there was a modest change in management (36%) compared with postoperative patients. This finding is in accordance with the few existing analyses on 68 Ga-PSMA PET/CT in therapynaïve patients before radiotherapy (19)(20)(21). In a recent analysis by Calais et al based on 73 patients with localized untreated prostate cancer, a major impact of 68 Ga-PSMA PET/CT was noted for 16.5% (12/73) of patients with intended irradiation of prostate, seminal vesicles, and pelvic lymphatic pathways and 37% of patients when radiotherapy fields covered prostate and seminal vesicles only (19).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in accordance with the few existing analyses on 68 Ga-PSMA PET/CT in therapynaïve patients before radiotherapy (19)(20)(21). In a recent analysis by Calais et al based on 73 patients with localized untreated prostate cancer, a major impact of 68 Ga-PSMA PET/CT was noted for 16.5% (12/73) of patients with intended irradiation of prostate, seminal vesicles, and pelvic lymphatic pathways and 37% of patients when radiotherapy fields covered prostate and seminal vesicles only (19). Likewise, Koerber et al presented data on the impact of 68 Ga-PSMA PET/CT on radiotherapy planning in 50 otherwise untreated prostate cancer patients (21).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Encouraging results of local or metastasis-directed therapy in patients with hormone-naïve oligometastatic recurrent PC [35,36] raise the question if oligoprogressive mCRPC patients may also benefit from local and/or metastasis-directed therapy [37][38][39]…”
Section: Psma-pet Targeted Local and Metastasis-directed Therapy In Tmentioning
confidence: 99%